P697 Examining the regulatory role of epigenetic and transcriptomic alterations in anti-TNFα treatment response and disease progression in patients with Ulcerative Colitis. (21st January 2022) - Lawal, O; Stack, R; Ciara, E; Tosetto, M; McDonnell, C; Rodriguez-Sosa, A; Yochum, G; Koltun, W; Boland, K; Sheahan, K; Doherty, G; Das, S
Abstract: Background: Ulcerative colitis (UC) is a chronic inflammatory condition characterized by significant morbidity and escalating economic costs. Effective patient management is severely hampered by a lack of unambiguous molecular biomarkers that can predict response to anti-TNFα treatment such and/or disease progression. While, both genetic and epigenetic factors have been reported to impact UC pathogenesis, their role in regulating disease progression and treatment response remains unclear. Methods: Here, we applied methyl-capture sequencing and RNAsequencing to mucosal biopsies derived from clinical cohorts of patients with mild-to-moderate and severe UC with the aim of identifying various regulatory factors that orchestrate treatment response and disease severity in these patients. Results: First, differential gene expression analysis between responders and non-responders to infliximab and vedolizumab (anti-TNFα) enabled identification of disease-associated genes that were either up- or down-regulated in responders to both these anti-TNFα agents. Next, upstream analysis of these differentially expressed genes revealed that both up- and downregulated genes in responders are intricately regulated by " master regulators " (MRs) including chemokine ligands and receptors such as FGFR2 and IL8 respectively. Moreover, we show that these MRs play a pivotal role in regulating gene expression through a complex signalling network mediated by transcription factors (TFs) such as FYN and ICAM1. These results for the first time provide evidence of impact of MRs and TFs on genes involved in differential response to anti-TNFα agents in patients with UC. In parallel, targeted DNA methylation profiling of mucosal biopsies derived from mild-to-moderate (n=85) and severe UC (n=33) patients enabled identification of a wide-spread DNA methylation alterations at regulatory regions such as promoters and enhancers. Moreover, we identified distinct significant methylation differences between UC patients who progress in their disease course leading to treatment with anti-TNFα/immunodulators agents vs. patients who are on 5'Asa maintenance treatment. Indeed, similar differences was also observed between responders and non-responders of anti-TNFαagents. Conclusion: Taken together, our preliminary results for the first time highlight the regulatory role of master regulator-mediated signalling networks involving transcription factors that regulate gene expression underpinning response to anti-TNFa in UC patients. In parallel, these results identify specific DNA methylation alterations that impact treatment response and disease severity and therefore could ultimately enact as predictive biomarkers in UC.